Effect of Preoperative Medical Status on Microsurgical Free Flap Reconstructions: A Matched Cohort Analysis of 969 Cases - Ehrl, Denis; Heidekrueger, Paul I.; Ninkovic, Milomir; Broer, P. Niclas (Journal of Reconstructive Microsurgery, 2018)
Background Free tissue transfers have become standard for a wide variety of reconstructive purposes. In an era of increasing economic pressure, it is important to precisely define appropriate candidates and indications for a complex surgery to optimize efficiency and patient outcomes. This study evaluates the feasibility to perform microsurgical procedures in a medically compromised patient cohort at a major academic microsurgical center.Methods Within 7 years, 897 patients underwent 969 microvascular free flap reconstructions. The data were retrospectively screened for patients' demographics, perioperative details, flap survival, surgical complications, and outcomes. The cases were divided into two groups in “low-risk” (American Society of Anesthesiologists [ASA] I and II) or “high-risk” (ASA III and IV) as per the preoperative medical status classified according to the ASA score of physical status.Results Despite the significantly high prevalence of hypertension, peripheral artery disease, diabetes, obesity, and smoking status in the “high-risk” group (p < 0.05), there was no significant difference in the rate of surgical or medical complications, in operative times regarding overall as well as different flap entities, flap failures, need for revision surgery, or hospital length of stay between the two patient groups during our 3-months follow-up period (p > 0.05).Conclusion In this study, free flap reconstruction in medically compromised patients was not associated with higher rates of revision surgeries, overall complication rates, or surgery-related costs. Complex microsurgical free flap reconstruction can therefore also be advocated in patients with high preoperative risk constellation.
Keywords: ASA score; free flap reconstruction; risk constellation